Emotion Regulation Difficulties and Academic Procrastination - Mohammadi Bytamar, Jahangir; Saed, Omid; Khakpoor, Sahel (Frontiers in Psychology, 2020)
Objective and Background. Academic procrastination as deliberate postponement of academic tasks, despite being aware of its consequences, is a common phenomenon among students. Current conceptualizations of procrastination support the rule of emotion regulation difficulties in the psychopathology of this phenomenon. In this regard, the current study is aimed to investigate the role of difficulty in emotion regulation in academic procrastination. Method. The present study is a cross-sectional study. Participants were 250 students who completed Tuckman Procrastination Scale (TPS), and Difficulties in Emotion Regulation Scale (DERS). Result. Correlation analyses showed that the TPS has a significant positive association on overall DERS and all but one of the six dimensions (DERS-Awareness) of emotion regulation difficulties (p < .01). This association remained significant after controlling for anxiety and depression. Further, the multivariate regression showed that the only DERS dimension that could predict TPS was DERS-Strategies. Finally, individuals with a high level of procrastination reported greater DERS scores than those with a lower level. Discussion. Results indicate that difficulty in emotion regulation, especially the ones' believe about his/her ability in regulating unpleasant emotions effectively, is important in procrastination. However, despite the limited association between DERS and TPS, the findings raise some potentially useful implications for procrastination studies and interventions.